2017
DOI: 10.1161/strokeaha.117.017513
|View full text |Cite
|
Sign up to set email alerts
|

Association of Computed Tomography Ischemic Lesion Location With Functional Outcome in Acute Large Vessel Occlusion Ischemic Stroke

Abstract: The association between follow-up noncontrast computed tomography ILV and outcome as assessed with mRS 3 months after stroke is strengthened by accounting for the mRS relevance of the affected brain areas. Future prediction models should account for the ILV in brain areas of high mRS relevance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 36 publications
1
41
1
Order By: Relevance
“…Nevertheless, if located within strategic brain regions such as the motor cortex or cortico spinal tract, even small lesions might have a relevant effect on clinical outcome. Thus, it has been found that infarct location in addition to core infarct volumes is a significant factor determining the clinical outcome [17].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, if located within strategic brain regions such as the motor cortex or cortico spinal tract, even small lesions might have a relevant effect on clinical outcome. Thus, it has been found that infarct location in addition to core infarct volumes is a significant factor determining the clinical outcome [17].…”
Section: Discussionmentioning
confidence: 99%
“…Second, infarct location assessment was restricted to follow-up ASPECTS regions combined with lateralization. A more detailed analysis on the location of brain tissue injury may improve the strength of the relation between FIV and functional outcome, as this more closely resembles brain eloquence 25. Finally, we compared different populations to assess the optimal imaging modality and timing for FIV measurement.…”
Section: Discussionmentioning
confidence: 99%
“…The goal of our study was to compare CoT versus ET in a real world single center cohort of AIS patients with LVO, exploring the safety profile of these two treatments and comparing their effect on radiological and functional outcomes [11,12].…”
Section: Introductionmentioning
confidence: 99%